Basketball's greatest players - Kramer, Sydelle (New York : Random House, 2003)
Describes how and why such men as Bill Russell, Wilt Chamberlain, and Larry Bird became great basketball players.
Keywords: Basketball players -- United States -- Biography -- Juvenile literature; Basketball players -- Rating of -- United States -- Juvenile literature; Basketball players